(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Antibiotics are harmful pharmaceuticals to ecosystems in general and aquatic systems in particular. Therefore, its remediation from water bodies is a topic of great importance for water treatment and purification workers. This research investigates the removal of one of the most famous types of antibiotics, which was tetracycline from simulated synthetic aqueous solutions by adsorption technique using non-toxic, low cost and available agricultural waste which was pomegranate peels. The adsorption experiments were performed in adsorption laboratory unit of batch mode at different operating conditions and laboratory temperature. The operating parameters studied included pH of solution, dose of adsorbent media, treatment time, agitation speed and initial concentration of tetracycline. The results showed the ability of pomegranate peels to extract tetracycline from aqueous solutions with high efficiency of 81.55%. The results also showed that the percentage of antibiotic adsorption from aqueous solutions was inversely correlated with increasing the initial concentration and acidic function of the tetracycline solution while it was directly proportional to the amount of pomegranate peels, agitation speed and treatment time. In this style, one of the most important types of antibiotics that contaminated water was disposed of by a cheap material and using a simple, economical and environmentally friendly method accessing to the principle of zero residue level (ZRL).